Water supply : considered mainly from a chemical and sanitary standpoint - Nichols, WM. Ripley (New York : John Wiley & Son, Inc., 2021)
This work has been selected by scholars as being culturally important and is part of the knowledge base of civilization as we know it. This work is in the public domain in the United States of America, and possibly other nations. Within the United States, you may freely copy and distribute this work, as no entity (individual or corporate) has a copyright on the body of the work. Scholars believe, and we concur, that this work is important enough to be preserved, reproduced, and made generally available to the public. To ensure a quality reading experience, this work has been proofread and republished using a format that seamlessly blends the original graphical elements with text in an easy-to-read typeface.
Chapter 1. Drinking water and disease -- Chapter 2. Water Analysis -- Chapter 3. Rain water as a source of supply -- Chapter 4. Surface waters as sources of supply -- Chapter 5. Surface water as sources supply -- Chapter 6. Ground water as source of supply -- Chapter 7. Deep seated water as a source of supply -- Chapter 8. Artificial Improvement of natural water -- Chapter 9. Artificial Improvement of natural water -- Chapter 10. Some General considerations.
Includes index.
Keywords: WATER SUPPLY